Rotating structures in low temperature magnetized plasmas—insight from particle simulations - Boeuf, Jean-Pierre (Frontiers in Physics, 2014)
The E × B configuration of various low temperature plasma devices is often responsible for the formation of rotating structures and instabilities leading to anomalous electron transport across the magnetic field. In these devices, electrons are strongly magnetized while ions are weakly or not magnetized and this leads to specific physical phenomena that are not present in fusion plasmas where both electrons and ions are strongly magnetized. In this paper we describe basic phenomena involving rotating plasma structures in simple configurations of low temperature E × B plasma devices on the basis of PIC-MCC (Particle-In-Cell Monte Carlo Collisions) simulations. We focus on three examples: rotating electron vortices and rotating spokes in cylindrical magnetrons, and azimuthal electron-cyclotron drift instability in Hall thrusters. The simulations are not intended to give definite answers to the many physics issues related to low temperature E × B plasma devices but are used to illustrate and discuss some of the basic questions that need further studies.